Integrons: Vehicles and pathways for horizontal dissemination in bacteria - Domingues, Sara (Landes Bioscience, 2012)
Integrons are genetic elements first described at the end of the 1980s. Although most integrons were initially described in human clinical isolates, they have now been identified in many non-clinical environments, such as water and soil. Integrons are present in ≈10% of the sequenced bacterial genomes and are frequently linked to mobile genetic elements (MGEs); particularly the class 1 integrons. Genetic linkage to a diverse set of MGEs facilitates horizontal transfer of class 1 integrons within and between bacterial populations and species. The mechanistic aspects limiting transfer of MGEs will therefore limit the transfer of class 1 integrons. However, horizontal movement due to genes provided in trans and homologous recombination can result in class 1 integron dynamics independent of MGEs. A key determinant for continued dissemination of class 1 integrons is the probability that transferred MGEs will be vertically inherited in the recipient bacterial population. Heritability depends both on genetic stability as well as the fitness costs conferred to the host. Here we review the factors known to govern the dissemination of class 1 integrons in bacteria.